Using natural travel paths to infer and compare primate cognition in the wild - Janmaat, K; de Guinea, M; Collet, J; Byrne, R; Robira, B; van Loon, E; Jang, H; Biro, D; Ramos-Fernandez, G; Ross, C; Presotto, A; Allritz, M; et al. (Cell Press, 2021)
Within comparative psychology, the evolution of animal cognition is typically studied either by comparing indirect measures of cognitive abilities (e.g., relative brain size) across many species, or by conducting batteries of decision-making experiments among (typically) a few captive species. Here, we propose a third, complementary approach: inferring and comparing cognitive abilities through observational field records of natural information gradients and the associated variation in decision-making outcomes, using the ranging behaviour of wild animals. To demonstrate the feasibility of our proposal, we present the results of a global survey assessing the availability of long term ranging datasets from wild primates and the willingness of primatologists to share such data. We explore three ways in which such ranging data, with or without the associated behavioural and ecological data often collected by primatologists, might be used to infer and compare spatial cognition. Finally, we suggest how ecological complexity may be best incorporated into comparative analyses.